PENGARUH ETOS KERJA DAN MOTIVASI TERHADAP KINERJA PANITIA DALAM PERSIAPAN PELAKSANAAN YUDISIUM DAN WISUDA KE V AK. MAPINDO TAHUN 2021 - Lindawati, Ni Putu; Ekadharma Susila, Bagus Putu (Jurnal Manajemen Pelayanan Hotel, 2021)
This study aims to determine the The Influence of Work Ethic and Motivation on the Performance of the Committee in Preparation for the Implementation of the 5th AK Judisium and Graduation MAPINDO 2021. The questionnaire distributed to 32 respondents was all members of the population. This study, using regression analysis techniques by testing hypotheses using t test and F test. The t-test results show that work ethic has a positive and significant effect on Committee in preparation for the implementation of the 5th AK Judisium and Graduation MAPINDO 2021. This is seen from the results of the regression coefficient X1(b1) tcount = 6,945 > ttable (0.05: 29) = 1,699 and sig t = 0,000 (p < 0.05). Motivation has a positive and significant effect on Committee in preparation for the implementation of the 5th AK Judisium and Graduation MAPINDO 2021. This is seen from the results of the regression coefficient X2(b2) tcount = 5,420> ttable (0.05: 29) = 1,699 and sig t = 0,000 (p <0.05). Work ethic and motivation have a positive and significant effect on Committee in preparation for the implementation of the 5th AK Judisium and Graduation MAPINDO 2021. This is based on the results of the F statistical test (ANOVA) where Fcount = 143,986 > Ftable = 3,33 with sig F = 0,000 (p < 0.05). Other information obtained from the results of the above analysis that work ethic has a more dominant influence performance achievement when compared with motivation . Keywords: Work Ethic, Motivation, Performance